Acute myocardial infarction following a hornet sting - Cvetković-Matić Danica; Ašanin Milika; Matić Dragan; Ivanović Branislava; Simić Dragan; Kalezić Nevena; Stojanov Vesna (Vojnosanitetski Pregled)
Background. The occurrence of an acute myocardial infarction following a hornet sting has been very rarely reported in the previous literature. Pathogenetic mechanisms include direct action of the venom components on the coronary endothelium and allergic reaction with mediators released from mast cells. The anaphylactic reaction and venom components can produce acute coronary artery thrombosis. Case report. We reported a 45-year-old man with acute myocardial infarction after a hornet sting in the presence of anaphylaxis. We also discussed clinical implications and pathophysiological mechanisms of acute myocardial infarction caused by hymenoptera sting. Conclusion. A case report of this unusual acute myocardial infarction highlights the potential acute myocardial ischemia associated with hymenoptera sting which requests early diagnosis, thorough cardiovascular evaluation and appropriate treatment.